A question of feedback? Studying effects of academic performance and teacher feedback on primary school students' social acceptance in an experimental setting - Nicolay, Philipp; Huber, Christian (Frontiers in Education, 2023)
Being socially accepted by peers is a fundamental psychological need and the consequences of social rejection are manifold. Investigating the causes of social rejection, a large body of studies already established the relationship between social acceptance and individual characteristics (e.g. academic performance). However, the overall contributions of those individual characteristics are rather small and the cause-and-effect relationship still unclear. In addition, following social referencing theory, studies suggest the feedback teachers give to students might also influence their social acceptance. This experimental study, therefore, examined the influence academic performance as well as teacher feedback have on social acceptance. Teacher feedback was operationalized along two dimensions: feedback valence (positive/negative) and feedback focus (personal/task). A total of 737 3rd and 4th-grade primary school students (51% female) from North Rhine-Westphalia (Germany) rated a fictional student's social acceptance on a scale of three sociometric items before and after watching an experimental video that showed one school day of the fictional student. Participants were randomly assigned to one level of academic performance (high/average/low) and one of four feedback conditions with each being a combination of the two factors feedback valence and feedback focus. Data was analyzed using linear mixed models. Results indicate that both academic performance, as well as the valence of teacher feedback, influenced participants' social acceptance towards the student in the video. A high academic performance had a positive and a low academic performance had a negative effect on social acceptance. Accordingly, positive teacher feedback influenced social acceptance positively while negative teacher feedback influenced social acceptance negatively. However, this effect was moderated by the focus of the This is a provisional file, not the final typeset article teacher feedback. Feedback with a focus on the person had a stronger effect on social acceptance for both positive and negative feedback than feedback with a focus on the task. These findings illustrate the importance teachers and their feedback have on students' peer relationships. They further suggest that it not only matters if teachers give positive or negative feedback but also how they do it.